Diel variation of formaldehyde levels and other VOCs in homes driven by temperature dependent infiltration and emission rates. (15th July 2019) - Huangfu, Yibo; Lima, Nathan M.; O'Keeffe, Patrick T.; Kirk, William M.; Lamb, Brian K.; Pressley, Shelley N.; Lin, Beiyu; Cook, Diane J.; Walden, Von P.; Jobson, Bertram T.
Abstract: High time resolution monitoring of formaldehyde and other volatile organic compounds in the air of four homes in winter and summer revealed diel variation of VOC levels driven by infiltration and temperature dependent whole house emission rates. In unoccupied homes, these pollutants displayed a large diel concentration variation, with an afternoon maxima and early morning minima. VOC abundance lagged about 2 h behind changes in infiltration rates measured by a tracer release method, resulting in poor correlations between VOC concentration and air change rate. The data demonstrate that VOC abundance was not in steady state with respect to whole house emission rates. Formaldehyde and other VOCs displayed a positive correlation with indoor temperature in both winter and summer. Formaldehyde sensitivity to temperature ranged from 3.0 to 4.5 ppbv per °C, a useful metric for predicting the impact of heat waves and changing regional climate on indoor air quality. Gypsum wallboard used as radiant ceiling heating product in one home was identified as source of formaldehyde and potentially mercury. Highlights: Diel variation of indoor formaldehyde and other VOCs were found. VOC levels are in dynamic state due to the time of day variation of infiltration rate. VOC levels lag behind the air change rate. Formaldehyde levels have temperature dependence of 3.0–4.5 ppbv per °C. Gypsum wallboard is a formaldehyde source when heated.